Etiology and management of Neofabraea lenticel decay (bull’s eye rot) of apples in the Western Cape of South Africa - Russouw, Andre (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.